2006
DOI: 10.1038/sj.jid.5700431
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization to the Yeast Malassezia Sympodialis Is Specific for Extrinsic and Intrinsic Atopic Eczema

Abstract: The opportunistic yeast Malassezia sympodialis belongs to the normal cutaneous flora but can also cause IgE-mediated sensitization in patients suffering from atopic eczema (AE). We investigated 706 individuals by ImmunoCAPm70 and skin-prick tests with a crude M. sympodialis extract. In AE patients, we further performed skin prick tests, atopy patch tests, ELISA, and peripheral blood mononuclear cells proliferation assays with recombinant M. sympodialis allergens (rMala s 1 and 5-9). In 52/97 patients with AE-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(78 citation statements)
references
References 52 publications
(53 reference statements)
2
75
0
1
Order By: Relevance
“…29 Third, patients may not be sensitized for inhalant or food allergens, but for microorganisms such as Staphylococcus aureus or Malassezia sympodialis, which are not detected by routine allergen panel tests. 40,41 In addition, absence of allergenspecific IgE can be explained by as yet unidentified allergens. For example, sensitization may exist for airborne fungal antigens derived from the Coprinus comatus.…”
Section: Discussionmentioning
confidence: 98%
“…29 Third, patients may not be sensitized for inhalant or food allergens, but for microorganisms such as Staphylococcus aureus or Malassezia sympodialis, which are not detected by routine allergen panel tests. 40,41 In addition, absence of allergenspecific IgE can be explained by as yet unidentified allergens. For example, sensitization may exist for airborne fungal antigens derived from the Coprinus comatus.…”
Section: Discussionmentioning
confidence: 98%
“…Analysis by ELISA indicated that the frequencies of positivity for IgE Abs to rMala s 1, 5, 6, 7, 8, and 9 were 39, 47, 55, 10, 31, and 61%, respectively, indicating that Mala s 1, 5, 6 and 9 are the predominant allergenic components. 129 …”
Section: Malasseziamentioning
confidence: 97%
“…147 In contrast, Mala s 1, 7, 8, and 9 are considered to be specific allergens with unique sequences. 129,144,148,149 Casagrande et al investigated the frequency of sensitization to a panel of recombinant M. sympodialis allergens (rMala s 1 and 5e9) in 51 patients with atopic eczema who were positive for IgE Abs to crude M. sympodialis (ImmunoCAP m70). Analysis by ELISA indicated that the frequencies of positivity for IgE Abs to rMala s 1, 5, 6, 7, 8, and 9 were 39, 47, 55, 10, 31, and 61%, respectively, indicating that Mala s 1, 5, 6 and 9 are the predominant allergenic components.…”
Section: Malasseziamentioning
confidence: 99%
“…have gathered attention in AD pathogenesis, and several studies have demonstrated that patients with AD have more reactive skin testing to Malassezia spp., more reactive to atopy patch testing to Malassezia spp., and have higher titers of Malassezia spp. specific IgE [52,[55][56][57]. Furthermore, positive skin prick testing against Sacchromyces cerevisiae has also been reported in patients with AD [40].…”
Section: Mold and Atopic Dermatitismentioning
confidence: 97%